2009
DOI: 10.1353/sof.0.0169
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Sociology of Racial Conceptualization for the 21st Century

Abstract: Despite their longstanding interest in race, American sociologists have conducted little empirical research on sociodemographic patterns or longitudinal trends in "racial conceptualization" -that is, notions of what race is, how races differ, and the origins of race. This article outlines key empirical, methodological and theoretical considerations for a research agenda on racial conceptualization. Drawing on in-depth interviews with more than 50 college students, I describe the variety of race concepts among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 40 publications
2
75
0
2
Order By: Relevance
“…As Morning (2009) defines it, race does not refer to any biological reality, but rather to a sociological grouping of certain individuals believed to share a common genealogical descent marked by certain shared phenotypical traits. Morning thereby distinguishes race from ethnicity, which, in the American context, is viewed as optional and symbolic, capable of being chosen and rejected, "with the knowledge that such identification will have little if any repercussions for major life outcomes" (Morning, 2008, p. 242; see also Gans, 1979;Waters, 2001).…”
Section: What Kind Of Category Is Islam?mentioning
confidence: 99%
“…As Morning (2009) defines it, race does not refer to any biological reality, but rather to a sociological grouping of certain individuals believed to share a common genealogical descent marked by certain shared phenotypical traits. Morning thereby distinguishes race from ethnicity, which, in the American context, is viewed as optional and symbolic, capable of being chosen and rejected, "with the knowledge that such identification will have little if any repercussions for major life outcomes" (Morning, 2008, p. 242; see also Gans, 1979;Waters, 2001).…”
Section: What Kind Of Category Is Islam?mentioning
confidence: 99%
“…Regarding the latter finding, several studies from different countries have indicated that white media users more readily employ stereotypical explanations (natural physicality) regarding black athletic performances (Harrison, Lawrence, and Bukstein 2011;Morning 2009). Regarding the differences between male and female athletes, both men and women are more eager to employ the hegemonic media discourse which emphasizes that men are naturally stronger and tougher than women (Knoppers and Elling 2001;Lines 2000).…”
Section: State Of Knowledge and Research Questionmentioning
confidence: 99%
“…Many higher education scholars and practitioners have aligned with the first camp in their promotion of identity as a socially constructed concept (Adams, Bell, & Griffin, 2007; Torres, Jones, & Renn, 2009), while biological explanations of identity have largely been rejected (McDonald, 2013;Tawa & Kim, 2011). College students are likely to be educated about race, gender, sexual orientation, and other identities through the paradigm of "social identities" (Jones & Abes, 2013) and social constructionism (Khanna & Harris, 2009;Morning, 2009). Despite this fact, students maintain conceptions rooted in biological explanations of race (Johnston, 2014;Morning, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…College students are likely to be educated about race, gender, sexual orientation, and other identities through the paradigm of "social identities" (Jones & Abes, 2013) and social constructionism (Khanna & Harris, 2009;Morning, 2009). Despite this fact, students maintain conceptions rooted in biological explanations of race (Johnston, 2014;Morning, 2009). As such, it is disconcerting that many scholars are dismissive of biological lines of inquiry related to identity, particularly race and gender, even though students themselves might place value on biological explanations of identity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation